Breast cancer prevention and management: Evidence and possibility in India - Amit Kumar Jain; Parvati Nandy (Wolters Kluwer Medknow Publications, 2019)
In India, cancer has become a new epidemic, with breast cancer topping the list. Prevention and management of this new epidemic is restrained with limited resources and heterogeneously concentrated cancer care in India. Technology can come to help for the above, and in this short communication below, we shall discuss the prevention and management of breast cancer with special reference to the use of technology for the same in the Indian context.